2014
DOI: 10.1158/1055-9965.epi-14-0458
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Profile and Risk of Prostate Cancer Recurrence: Results from the SEARCH Database

Abstract: Background: Evidence for an association between total cholesterol, low-and high-density lipoproteins (LDL and HDL, respectively), triglycerides, and prostate cancer is conflicting. Given that prostate cancer and dyslipidemia affect large proportions of Western society, understanding these associations has public health importance.Methods: We conducted a retrospective cohort analysis of 843 radical prostatectomy (RP) patients who never used statins before surgery within the Shared Equal Access Regional Cancer H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 30 publications
5
113
1
1
Order By: Relevance
“…A substantial body of evidence supports an association between obesity and various cancers, including CRC [19]. Elevated serum cholesterol levels were shown to be linked to a higher risk of developing certain cancers, and higher cholesterol levels may also increase cancer recurrence [20, 21]. Moreover, statins use in patients with cancer is associated with a reduced cancer-related mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence supports an association between obesity and various cancers, including CRC [19]. Elevated serum cholesterol levels were shown to be linked to a higher risk of developing certain cancers, and higher cholesterol levels may also increase cancer recurrence [20, 21]. Moreover, statins use in patients with cancer is associated with a reduced cancer-related mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previously in this cohort, we reported that elevated triglycerides were associated with increased risk of prostate cancer recurrence among all men, while high cholesterol, high low-density lipoprotein (LDL) and low high-density lipoprotein (HDL) were associated with increased risk of recurrence only among men with dyslipidemia [17]. However, due to limited numbers of patients in our prior study, we were unable to test whether associations differed between black and non-black men.…”
Section: Introductionmentioning
confidence: 87%
“…The SEARCH database is a retrospective cohort of prostate cancer patients undergoing radical prostatectomy at six Veterans Administration (VA) Medical Centers (West Los Angeles, CA; Palo Alto, CA; San Diego, CA; Durham, NC; Asheville, NC; and Augusta, GA) [17]. Institutional Review Board approval was obtained to abstract and analyze the data.…”
Section: Methodsmentioning
confidence: 99%
“…PSA relapse) following prostatectomy in 843 patients who had never received statins prior to their surgery. They found that elevated triglycerides were associated with increased risk of recurrence for the entire cohort, and that an elevated total cholesterol level was associated with an increased risk for those with hyperlipidemia [Allott et al 2014]. While this finding is consistent with statins exerting a beneficial antitumor effect through lowering lipids, it does not specifically address whether or not statins modulate SLCO transporter activity.…”
Section: Statins and Androgen Transporter Activitymentioning
confidence: 99%
“…Several epidemiologic and retrospective studies have been completed to specifically evaluate for an association between statin use and the development of prostate cancer [Flick et al 2007;Boudreau et al 2008;Chang et al 2011;Allott et al 2014;Jespersen et al 2014;Chan et al 2015;Cuaron et al 2015;Kantor et al 2015;Luo et al 2015;Sun et al 2015;Zapata et al 2015]. In general, these studies have supported the notion that statins may function as a prostate cancer chemoprotective agent; however, some data conflict with this assertion.…”
Section: Statin Use and Cancer Riskmentioning
confidence: 99%